Agility versus Maturity: Is There Really a Trade-Off? - Vinekar, Vishnu; Huntley, Christopher L. (Computer (00189162), 2010)
The article focuses on the reasons why software developers are not following agile or formal methods as traditionally conceptualized. It cites the challenges faced by organizations in switching to a purely formal approach and a purely agile one. It mentions the increasing demand for the so-called agile tools to meet the needs of top management. According to emerging empirical evidence, most agile teams utilize some upfront design while most formal methods are iterative.